(untitled) (Janaki Medical College Journal of Medical Science, 2024)
Surfactant is a complex mixture of phospholipids, mainly dipalmitoylphosphatidylcholine (DPCC) and surfactant proteins (SP); SP-A, SP-B, SP-C, and SP-D. DPCC plays a crucial role in lowering the surface tension, while SPs provide immunity against invading pathogens. SPs also enhance the activity of phospholipids, aiding in the adsorption and spread of surfactants all over the alveolar surface. Surfactant production starts as early as 24 weeks of gestation in humans and peaks at about 36-38 weeks. The generation and secretion of lung surfactants are tightly regulated processes. Surfactant is synthesized by type II alveolar cells and stored in lamellar bodies. Following stimulation, these lamellar bodies combine with the cell membrane and release their content into the alveolar spaces. Respiratory distress syndrome (RDS) is a fatal disease that primarily occurs in premature infants, and is mainly caused by the absence or dysfunction of pulmonary surfactant. The alveoli collapse due to surfactant insufficiency impairs the gas exchange in RDS causing respiratory failure. One of the treatment options for RDS in preterm infants is surfactant replacement therapy (SRT), where exogenous surfactant preparations are given to replete the levels of surfactant in the lungs. Prophylactic corticosteroids given at about 24 to 34 weeks of gestation to the pregnant mother may prevent surfactant deficiency in babies as it hastens surfactant production. In this review, we have explored the role of surfactants in the normal functioning of the lungs and different disease conditions.